Establishment of the interferon-mediated antiviral state: role of fatty acid cyclooxygenase. - Pottathil, R (1980)
Inhibitors of fatty acid cyclooxygenase 8,11,14-icosatrienoate, hydrogen donor:oxygen oxidoreductase, EC 1.14.99.1) were found to suppress the establishment of the interferon-mediated antiviral state. The prevention, by these compounds, of the development of interferon protection correlated with the degree as well as the duration of cyclooxygenase inhibition. Anti-inflammatory substances lacking cyclooxygenase inhibitory activity did not interfere with the establishment of interferon protection. The addition of exogenous prostaglandins was not found to replace the need for a functional cyclooxygenase and, in some instances, could be shown to diminish the establishment of interferon protection. It is proposed that fatty acid cyclooxygenase is an essential component in the optimal induction of the interferon antiviral state.